2022
DOI: 10.3389/fonc.2022.803493
|View full text |Cite
|
Sign up to set email alerts
|

HOXB4 Mis-Regulation Induced by Microcystin-LR and Correlated With Immune Infiltration Is Unfavorable to Colorectal Cancer Prognosis

Abstract: Microcystin-LR (MC-LR) exists widely in polluted food and water in humid and warm areas, and facilitates the progression of colorectal cancer (CRC). However, the molecular mechanism associated with the MC-LR-induced CRC progression remains elusive. The purpose of this study is to explore the role of the hub genes associated with MC-LR-induced CRC development at the molecular, cellular and clinical levels through bioinformatics and traditional experiments. By utilizing R, we screened and investigated the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…8G-8L), which is consistent with previous studies reporting that high HOXB4 expression promotes cell proliferation and migration, drives cell cycle progression, and is associated with poorer survival probability. In addition, studies have shown that HOXB4 is involved in immune in ltration, especially in tumor-associated macrophages and cancer-associated broblasts [32]. Our analysis of the tumor immune microenvironment indicated that patients with high HOXB4 expression have high in ltration in some immune cells (such as CD8 T cells, macrophages, NK cells, etc.…”
Section: Discussionmentioning
confidence: 63%
“…8G-8L), which is consistent with previous studies reporting that high HOXB4 expression promotes cell proliferation and migration, drives cell cycle progression, and is associated with poorer survival probability. In addition, studies have shown that HOXB4 is involved in immune in ltration, especially in tumor-associated macrophages and cancer-associated broblasts [32]. Our analysis of the tumor immune microenvironment indicated that patients with high HOXB4 expression have high in ltration in some immune cells (such as CD8 T cells, macrophages, NK cells, etc.…”
Section: Discussionmentioning
confidence: 63%
“…ERBB2 [114], CAV1 [152], SOCS3 [150], HNF4A [133], hsamir-449a [503], hsa-mir-21 [504], NUCKS1 [505], NANOG (Nanog homeobox) [506], IRF8 [507] and SMAD4 [508] were a diagnostic markers of ulcerative colitis and could be used as therapeutic targets. ERBB2 [172], BIRC3 [192], IFIT1 [509], SPRY2 [222], MAPK14 [306], E2F1 [325], CDC25A [294], CAV1 [301], BCL6 [297], CDKN1A [326], SOCS3 [293], HNF4A [244], hsa-mir-449a [503], hsa-mir-375 [510], hsa-mir-21-5p [511], hsa-mir-21 [512], NUCKS1 [513], HOXB4 [514], MECOM (MDS1 and EVI1 complex locus ) [515], NANOG (Nanog homeobox) [506], DNAJC2 [516], RAD21 [517], IRF8 [507] and SMAD4 [518] were found to be substantially related to gastrointestinal cancers. BIRC3 [482] , RPS26 [501], HOXB4 [519] and SMAD4 [520] might be associated with the prognosis of anemia.…”
Section: Identification Of Degsmentioning
confidence: 99%
“…During the overgrowth of HCBs, toxin-producing cyanobacteria release various microcystins (MCs) into the water body, with MC-LR, MC-RR, and MC-YR being the most toxic and widely distributed MC variants (Hoeger et al, 2007;Atencio et al, 2008;Zeller et al, 2012;Okogwu et al, 2014;He et al, 2018;Tao et al, 2018;Zhang et al, 2021). MCs are potent liver toxins and tumor promoters (Fujiki and Suganuma, 1994;Zhang et al, 2012;Tian et al, 2013;Wang et al, 2014Wang et al, , 2022Hernandez et al, 2021). These cyanotoxins are extremely stable and are not effectively removed by conventional methods.…”
Section: Introductionmentioning
confidence: 99%